IMPLEMENTASI ETIKA BISNIS PERSPEKTIF ISLAM - Khoiruddin, Khoiruddin (IAIN Salatiga, 2013)
Islamic business and economic ethics was one of book which was referring to Al Qur'an and following rasullullah Saw in business, finance, and economy.